Pengaruh Estim Kendiri, Aspirasi Kerjaya Dan Kepuasan Kerjaya Terhadap Resiliensi Kerjaya Dalam Kalangan Orang Kurang Upaya Pendengaran - Abd Rahman, Norhafisah (2021)
Employment is an important aspect to meet the needs of life whether normal or disabled. This research aimed to investigate the influence of self-esteem, career aspirations and career satisfaction on career resilience among people with hearing disabilities (PWHD).